2004
DOI: 10.1152/physiolgenomics.00177.2003
|View full text |Cite
|
Sign up to set email alerts
|

Screening anti-inflammatory compounds in injured spinal cord with microarrays: a comparison of bioinformatics analysis approaches

Abstract: Inflammatory responses contribute to secondary tissue damage following spinal cord injury (SCI). A potent anti-inflammatory glucocorticoid, methylprednisolone (MP), is the only currently accepted therapy for acute SCI but its efficacy has been questioned. To search for additional anti-inflammatory compounds, we combined microarray analysis with an explanted spinal cord slice culture injury model. We compared gene expression profiles after treatment with MP, acetaminophen, indomethacin, NS398, and combined cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 74 publications
(100 reference statements)
0
12
0
Order By: Relevance
“…The pattern of transcript expression was highly orchestrated from 1 to 90 d after injury and consistent in two distinct rat strains. As seen with thoracic contusions (Carmel et al, 2001;Song et al, 2001;Nesic et al, 2002;Tachibana et al, 2002;Di Giovanni et al, 2003;Pan et al, 2004), a profound loss of neural gene expression was observed by 1 d post-SCI. In our longitudinal study, a very modest rebound occurred by 90 d postinjury, reflective of neural tissue loss within the lesion.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The pattern of transcript expression was highly orchestrated from 1 to 90 d after injury and consistent in two distinct rat strains. As seen with thoracic contusions (Carmel et al, 2001;Song et al, 2001;Nesic et al, 2002;Tachibana et al, 2002;Di Giovanni et al, 2003;Pan et al, 2004), a profound loss of neural gene expression was observed by 1 d post-SCI. In our longitudinal study, a very modest rebound occurred by 90 d postinjury, reflective of neural tissue loss within the lesion.…”
Section: Discussionmentioning
confidence: 93%
“…Other SCI microarray (Carmel et al, 2001;Song et al, 2001;Tachibana et al, 2002;Pan et al, 2004) and directed studies (Popovich et al, 1996;Huang et al, 1999;Bethea, 2000;Bethea and Dietrich, 2002;Jones et al, 2002;Pan et al, 2002;Schwartz and Hauben, 2002;Hausmann, 2003) have shown that inflammation plays a major role in acute SCI. Our dataset further demonstrates the apparent regulatory roles of major cytokine families, the extensive orchestration of the immune response, its interrelationship with repair gene families, and a previously unreported persistence of this response in the subacute and chronic stages of SCI (Table 1, supplemental material, available at www.jneurosci.org).…”
Section: Discussionmentioning
confidence: 99%
“…Relative quantitation of spleen mRNA for the T-cell cytokines IFN␥ and IL-2 used a validated quantitative reverse transcription (RT)-PCR method as described previously by others at the Keck Center for Collaborative Neuroscience, Rutgers University (Pan et al, 2004). Wild-type (n ϭ 8) and mutant (n ϭ 8) mice were given injections of saline (n ϭ 4/strain) or 10 g of SEA (n ϭ 4/strain), and the spleens removed 2 h later.…”
Section: Reverse Transcription and Real-time Pcr For Splenic Ifn-␥ Anmentioning
confidence: 99%
“…A previous study used microarray approach to assess the genes involved in anti-inflammatory responses in a spinal cord injury model [28]. The anti-inflammatory response is an important component of secondary tissue damage following spinal cord injury.…”
Section: Discussionmentioning
confidence: 99%
“…To circumvent this limitation, we have recently sequenced more than 10, 000 ESTs (expression sequence tags) from the CNS transcriptome of L. stagnalis [20] and established the largest neuronal EST database in Lymnaea (http://www.lymnaea.org). In combination with the availability of the microarray technology [28,29], these gene sequences provide us with the opportunity to perform a high-throughput screening for altered gene expression levels following nerve injury in L. stagnalis . In this study, we have designed the first microarray chip covering 10, 333 known L. stagnalis genes to profile the gene expression patterns following CNS injury.…”
Section: Introductionmentioning
confidence: 99%